Conflict handling strategies in emotional key. - Montes, Carlos; Rodríguez, Dámaso; Serrano, Gonzalo (Anales de Psicología / Annals of Psychology, 2013)
Conflict is a dynamic and complex process emotionally actived. Therefore, in order to understand conflict management processes, it is necessary to study the influence of emotional variables which surround confrontations. The purpose of this paper is to explore how mood can influence the choice of conflict management strategies. Unlike other studies that artificially manipulate emotions, this one focuses on the differences in emotional experience that occur naturally. Results suggest that moods influence the choice of conflict handling strategies. Specifically, it has been found that positive affect predicts integrating, while negative affect predicts dominating. In conclusion, it is suggested that the intrapersonal influence of emotions is particularly noticeable when people experience high-aroused affective states.